PREDICTORS OF PROCRASTINATION IN THE PROFESSIONAL ACTIVITY OF SPECIALISTS OF SOCIONOMIC PROFESSIONS - Svitlana A. Nakhod (Alfred Nobel University Publisher, 2021)
The article considers the predictors of procrastination in the professional activity of specialists of socionomic professions. In the study, procrastination is defined as a personal disposition that manifests itself in human activities and behavior and is characterized by the postponement of significant matters. It is interconnected with personality traits, features of motivation and has development patterns, associated with age. It has been established that socionomic professions are professions aimed at solving problems related to social relations. Their content focuses on the development, regulation, study of social patterns and trends, preservation and transformation of historically defined and accepted forms of culture and traditions at all levels of social interaction. The peculiarities of the professions of psychologist, teacher, social worker and lawyer in the context of the outlined issues are clarified. These include: 1) the presence of interaction between people and social groups that differ in social positions and roles; 2) communication mediated by the goals pursued by each party; 3) prosocial activity of the personality of the specialist, which has become a set of motives for professional activity; 4) the focus of the specialist on the achievement of such humanistic and social ideals as well-being, health, high quality of life, effective development of individuals and groups in various formations of individual and social life. Given the specific features of socionomic professions, the search for predictors of procrastination was conducted among professionally significant personality traits of such specialists, including typical forms of behavior in work situations, attitude to certain aspects of the job, the presence of occupational stress symptoms and related deformations. The personal characteristics that affect the severity of procrastination of specialists were determined, including the obligation, determination, control, modesty, anxiety. It was found that a negative perception of the peculiarities of professional activity and a high level of occupational stress affects the manifestation of procrastination in specialists of socionomic professions. Low self-regulation is defined as the predictor of procrastination, and the tendency to delay is associated with all functional components that ensure the effectiveness of activities: planning, modeling, programming, evaluation of results, flexibility, independence. The connection between procrastination and perfectionism of specialists in socionomic professions has been established. It is concluded that the understanding of predictors of the phenomenon of procrastination of specialists of socionomic professions will contribute to the development of effective ways to overcome it in a certain category of experts, which will be the subject of our further research.